Empowering Communities Globally through Revolutionary Grain Processing: Memberdayakan Masyarakat Secara Global melalui Pemrosesan Biji-bijian yang Revolusioner - Irawan, Yuriza Rahayu; Husna, Rofiatul; Dewi, Linda Intania; Sischasari, Dyah; Istiningrum , Dyah (Indonesian Journal of Innovation Studies, 2024)
This research investigates economic empowerment strategies in Kedungpeluk village, Sidoarjo, focusing on processing grain yields to enhance local livelihoods. Utilizing a qualitative method based on literature review, the study identifies challenges and proposes solutions for operators of grain processing enterprises. Results indicate that processing excess grain into ready-to-eat products like abon, dendeng, and rempeyek udang can prevent spoilage and increase market value. The use of modern equipment and independent tambak cultivation is recommended to streamline production and increase self-reliance. The study suggests that these strategies, along with online marketing and product diversification like Korean food, can significantly improve local economic conditions. Collaboration with the government and utilization of digital marketing channels are also highlighted as essential for enhancing market share and economic empowerment in the community. Highlights: Value Addition: Process grain into high-value products to prevent spoilage. Self-Reliance: Use modern equipment for efficient, independent production. Market Expansion: Diversify products, employ online marketing for economic growth. Keywords: Economic empowerment, Grain processing, Livelihood enhancement, Local development, Community resilience